Biofilm consumption shapes the intestinal microbiota of shrimp (Penaeus vannamei). (18th December 2018) - Garibay‐Valdez, Estefanía; Martínez‐Córdova, Luis R.; Vargas‐Albores, Francisco; Gollas‐Galván, Teresa; Lago‐Leston, Asunción; Calderón, Kadiya; Martínez‐Porchas, Marcel
Abstract: The effect using biofilm as complementary feed for shrimp ( Penaeus vannamei ) on the taxonomic and functional profile of its intestinal microbiota was evaluated. Shrimp were cultured for 30 days in two similar low‐water exchange systems, one using commercial feed and the other a combination of commercial feed with biofilm as complementary feed source. Six bacteria phyla were detected in the intestine of shrimp from both treatments (Actinobacteria, Bacteroidetes, Cyanobacteria, Firmicutes, Fusobacteria and Proteobacteria), being Proteobacteria the most abundant (81%–92%). However, this later phylum was significantly less dominant in shrimp fed with biofilm; this drop was associated with a decrease in Vibrio abundance. Differences in the taxonomic profile of bacteria between treatments were also observed through principal component analysis where the diet was the main influencing factor (PC1 72.4%). Regarding functional inference, similarities were detected between treatments. Carbohydrate and energy metabolism were the most abundant functions regardless of time or diet, followed by metabolism of cofactors and vitamins, translation processes, nucleotide metabolism and others. Results suggest that biofilm consumption influenced the taxonomic profile bacteria colonizing the shrimp intestine; however, a functional redundancy was observed despite the use of biofilm as complementary feed. Finally, shrimp fed with biofilm showed a better productive response.